Edgeworthia gardneri (Wall.) Meisn. Water Extract Ameliorates Palmitate Induced Insulin Resistance by Regulating IRS1/GSK3β/FoxO1 Signaling Pathway in Human HepG2 Hepatocytes - Zhang, Yi; Yan, Li Shan; Ding, Yu; Cheng, Brian Chi Yan; Luo, Gan; Kong, Jing; Liu, Tong Hua; Zhang, Shuo Feng (Frontiers in Pharmacology, 2020)
The flower of Edgeworthia gardneri (Wall.) Meisn is commonly used in beverage products in Tibet and has potential health benefits for diabetes. However, the mechanisms underlying anti-insulin resistance(IR) action of the flower of Edgeworthia gardneri is not fully understood. This study aims to investigate the effects of the water extract of the flower of Edgeworthia gardneri (WEE) on IR in palmitate (PA)-exposed HepG2 hepatocytes. WEE was characterized by UPLC analysis. PA-treated HepG2 cells was selected as the IR cell model. The cell viability was determined using MTT assay. Moreover, the glucose consumption and production were measured by glucose oxidase method. The glucose uptake and glycogen content were determined by the 2-NBDG glucose uptake assay and anthrone-sulfuric acid assay, respectively. The intracellular triglyceride content was detected by oxidative enzymic method. Protein levels were examined by Western blotting. Nuclear localization of FoxO1 was detected using immunofluorescence analyses. The expression of FoxO1 target genes was detected by quantitative real-time polymerase chain reaction (qRT-PCR). The viability of PA-treated HepG2 cells was concentration dependently increased by incubation with WEE for 24 h. WEE treatment remarkably increased the consumption and uptake of glucose in PA-exposed HepG2 cells. Moreover, treatment with WEE significantly decreased the PA-induced over-production of glucose in HepG2 cells. After exposure of HepG2 cells with PA and WEE, the glycogen content was significantly elevated. The phosphorylation and total levels of IRβ, IRS1, and Akt were up-regulated by WEE treatment in PA-exposed HepG2 cells. The phosphorylation of GSK3β was elevated after WEE treatment. WEE treatment also concentration dependently down-regulated the phosphorylated CREB, ERK, c-Jun, and JNK in PA-exposed HepG2 cells. Furthermore, the nuclear translocation of FoxO1 was also suppressed by WEE. Additionally, PA-induced changes of FoxO1 targeted genes were also attenuated by WEE treatment. The GLUT2 and GLUT4 translocation were also promoted by WEE treatment. Taken together, WEE has potential anti-IR effect in PA-exposed HepG2 cells, the underlying mechanism of this action may be associated with the regulation of IRS1/GSK3β/FoxO1 signalling pathway. This study provides a pharmacological basis for the application of WEE in the treatment of metabolic diseases such as type 2 diabetes mellitus.